The Inkas as Tyrants: The Construction of a Twisted Representation - Fossa, Lydia (TTR)

(untitled) (Association canadienne de traductologie, 2005)
AbstractThe chronicler Pedro Sarmiento de Gamboa wrote a history of the Inkas in 1571 proving that they had been tyrants. This was necessary to convince the King that he had every right to appropriate their lands, riches, and peoples. It is an excellent example of how a representation does not necessarily have to match what actually happened when political issues are at stake. My article analyzes that twisted representation and explores the motives Sarmiento had for kuraka to authenticate his version.